Policy-Making in Metropolitan Areas: The Aniene River as a Green Infrastructure between Roma and Tivoli - Rizzo, Biancamaria (International Studies. Interdisciplinary Political and Cultural Journal, 2017)
The European policies acknowledge greenways and “Green Infrastructure” as strategically planned and delivered networks comprising the broadest range of green spaces and other environmental features. The Aniene River, linking the eastern suburbs of Rome to the City of Tivoli, has been envisaged in a multi-level approach as a Green-Blue Infrastructure able to hinder land use fragmentation and provide new continuity to remainders of open space. In turn, landscape is taken into account as a biodiversity reservoir, the scenery of outstanding cultural heritage and the relevant backdrop of ordinary life.